Incidence, associated factors and outcomes of antepartum hemorrhage at Ayder Comprehensive Specialized Hospital and Mekelle General Hospital, Mekelle, Tigray, Ethiopia - Hagos Hailu; Girmatsion Fisseha; Gelila Goba; Hale Teka; Sumeya Ahmed; Yemane, Awol (Ethiopian Journal of Reproductive Health, 2023)
Introduction: The leading cause of maternal mortality in world is obstetric hemorrhage. Antepartum hemorrhage (APH) is defined as bleeding from or into the genital tract after 28weeks of pregnancy and before delivery of the baby. Placenta previa and Abruptio placenta are the two major causes of antepartum hemorrhage worldwide including Ethiopia, and contribute significantly to obstetric hemorrhage which is the most common cause of maternal death in developing countries like Ethiopia. Hence, the present study is planned to assess the incidence, associated factors and outcomes of APH at ACSH and Mekelle general hospital. Objective: To assess incidence, associated factors and outcomes of APH at Ayder comprehensive specialized hospital and Mekelle general hospital, Mekelle, Tigray, Ethiopia Methodology: Hospital based prospective cross sectional (observational) was carried out at Ayder comprehensive specialized hospital and Mekelle general hospital over a period of 6 months from February 01, 2018 to July 30, 2018 on all pregnant mothers who were admitted to labor and maternity ward with the diagnosis of antepartum hemorrhage. Results: There were a total of 5368 deliveries in both Ayder comprehensive specialized hospital and Mekelle general hospital over a period of six months between February, 1/2018 to July, 30/2018. During this period, 192 mothers were diagnosed to have APH making incidence of 3.8 %. The major causes of APH were abruptio placenta in 89 (46.5 %) and placenta previa in 64 (33.3 %). Anemia and PPH were the main maternal complications, each accounting for 98(51 %) and 25 (13 %) respectively. There was one maternal death (0.5 %). Of the total 200 newborns, 26 (13 %) were stillbirth and there were 19 (9.5 %) of early neonatal deaths that died in the first seven days of life after admission to NICU making PMR of 22.5 %. Conclusion: APH which is primarily caused by abruptio placenta and placenta previa significantly affects the maternal and perinatal outcomes ACSH and MGH compared to reports from other countries. Maternal address out of Mekelle, severe maternal anemia, and abruptio placenta are predictors of increased perinatal mortality.